Combined opioid-sodium aescinate therapy in blunt thoracic trauma: retrospective evaluation - Zhang, Jun; Yan, Yijie; Guan, Zhiyu (Frontiers in Pharmacology, 2025)
BackgroundEffective analgesia is crucial for patients with blunt thoracic trauma, yet the optimal analgesic approach remains controversial. This study aimed to evaluate the efficacy of opioids combined with Sodium Aescinate in blunt thoracic trauma management.MethodsFifty patients with blunt thoracic trauma were randomly assigned to receive either opioids alone (morphine hydrochloride sustained-release tablets (MHST), Group A) or opioids combined with Sodium Aescinate (Group B). Pain scores, respiratory parameters, complications, and hospitalization metrics were assessed.ResultsWhen pain number rating scale (NRS) scores reached ≤4, Group B required significantly lower opioid doses throughout therapy. Group B demonstrated significantly higher FEV1, FVC, and arterial PO2, and lower PCO2 compared to Group A, while respiratory rates remained similar between groups. Opioid-related complications (nausea, constipation) were significantly reduced in Group B, which also experienced shorter hospital stays and lower costs.ConclusionThis study demonstrated synergism between opioids and Sodium Aescinate in providing effective analgesia. The combination therapy offers an efficient and economical approach for pain management in blunt thoracic trauma, with improved respiratory function and reduced opioid-related complications.